Workplace Spirituality and Employee Work Ethic: Key Success Factors at X Equipment Store, Gunungkidul - Hambawani, Ayuningtyas Diah; Warastri, Annisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research focuses on the relationship between spirituality in the workplace and the work ethic of employees at equipment shop X in Wonosari, Gunungkidul, Yogyakarta. Based on observations and interviews with 9 employees, it was found that the work ethic of employees in this shop was relatively low. Employees often neglect customer service, express emotions, differentiate customers based on appearance, and ignore the prayer hours that are regulated in company regulations. This shows that the low work ethic of some employees is influenced by low spiritual awareness in the workplace. The results of this study indicate a significant relationship between workplace spirituality and employee work ethic. Based on the research results, there is a positive relationship between Workplace Spirituality and Work Ethic, with a correlation coefficient = 0.557 (p> 0.50), meaning there is a significant positive relationship. Increasing spiritual awareness can improve the quality of work ethic, which has a positive impact on employee performance. This research suggests that companies can improve employee work ethics by strengthening spirituality in the workplace, which includes understanding the meaning and purpose of work and applying spiritual values in daily activities